DISIPLIN KERJA, KEMAMPUAN KOMUNIKASI, LINGKUNGAN KERJA: PENGARUHNYA TERHADAP KINERJA KARYAWAN PT. SANDHY PUTRA MAKMUR - Widowati, Prita Anugrah (Media Mahardhika, 2018)
The purpose of this study was to determine the influence of employee discipline, communication skills, and work environment of employees on employee performance. The variable in this study is the Work Discipline (X1), communication ability (X2), Working Environment (X3) and Performance (Y). The population in this study were all employees of PT. Sandhy Putra Makmur Surabaya Branch total of 39 people. Because the population is not so great in this study the authors took a sample with a sample system is saturated or Census Sampling. Analysis technique used is the Multiple Linear Regression Analysis. From the results of multiple linear regression analysis, it can be seen that 94.3% variable performance will be affected by the independent variable, namely employee discipline (X1), communication skills (X2) and work environment (X3). By t test or individually (partial), work discipline variable (X1) variable communication ability (X2) and work environment variables (X3) is equally significant effect on performance (Y). The results also show that the work environment is the dominant variable affecting the performance compared to the other variables.